Desarrollo Socio-Económico y su incidencia en la migración de los habitantes de la Comunidad Pulucate Alto, Parroquia Columbe, Cantón Colta, Provincia de Chimborazo desde el año 2010 al 2014. - Malan Chucuri, Franklin Geovanny (2016)
The research work is to examine how social economic conditions influence the migration of people from Pulucate Alto community, Colta canton, Chimborazo province. The farmer conditions in this zone live in poverty and misery, because the sale of the few products, which cultivates does not compensate or cover basic needs such as food, housing, clothing, health and others. Facing this reality, the vast majority of community members migrated to big cities: Guayaquil, Cuenca, and Riobamba and abroad: United States, Venezuela and Spain. This migration at that time contributed to the country's economy, and families. Another sector of people decided to go to other cities to work and make more money that in agriculture and therefore to support the family. People, who left the community, have gone to the cities to continue studies, get a job, and improve their lifestyle and their families. But a minority has created its own business or microenterprise, others are involved with construction, handicrafts and domestic jobs, resulting in the abandonment of homes, causing desolation and depopulation of Pulucate Alto, family disorganization and behavioral problems of children and young people who have no parental figure and feel the vacuum left by them